Pemanfaatan Simulasi PhET Berbantuan LKPD sebagai Media Pembelajaran Interaktif pada Materi Bandul Matematis - M. Salsabillah Hidayah; Said Wahyudi; M Gita Ahzami; Gunawan Gunawan (Indonesian Journal of Education and Community Services, 2026)
Physics is often perceived as a challenging subject by students due to the abstract nature of its concepts and the limited availability of physical laboratory facilities in schools. This study aims to examine student engagement, learning activity, and conceptual understanding through the integration of the PhET interactive virtual laboratory (Pendulum Lab) paired with guided student worksheets on the topic of the simple pendulum. A descriptive observational design was employed, involving students at State Senior High School 1 Praya Tengah. Data were collected using observational sheets to evaluate learning activities and document analysis of the students' group worksheets. The findings indicate that incorporating PhET simulations enhanced interactivity, heightened student enthusiasm, and enabled students to visualize abstract physics concepts more concretely. Guided by structured worksheets, students were able to independently analyze inter-variable relationships, confirming that string length and gravitational acceleration directly affect the pendulum’s period, whereas the mass of the bob has no effect. The study concludes that pairing PhET simulations with guided student worksheets provides an effective, innovative instructional tool to simplify abstract concepts and offers a viable alternative to overcome physical laboratory constraints in secondary education.